Akuntansi untuk Santri: Pelatihan Manajemen Keuangan Pribadi dan Usaha Kecil - Adi Supriadi; Dyatmiko, Ruruh; Hunein, Hamida (Abdimisi, 2025)
This community service activity aims to improve the financial literacy and basic accounting skills of Islamic boarding school students through accounting training for students: personal financial management and small business training. Students, as the younger generation with the potential to become economic drivers of Islamic boarding schools and the community, often lack an adequate understanding of financial management. This training is designed to equip participants with practical knowledge of personal financial planning, simple transaction recording, business cash management, and the preparation of basic financial reports. The activity methods include material delivery, transaction recording simulations, case discussions, and direct mentoring. The results of the activity show an increase in students' understanding of managing finances in a more structured manner and the ability to use simple recording tools for personal needs and small businesses. This activity is expected to encourage students' economic independence and create a healthier financial management culture within the Islamic boarding school environment. Keywords: Small Business Accounting, Financial Management, Financial Literacy